Luxury Fashion Theory, Culture, and Brand Marketing Strategy - Woodside, Arch; Ko, E. (Emerald Group Publishing Limited, 2013)
This article describes the core tenets of fashion marketing theory (FMT) from the perspective of economic psychology. The study here is unique and valuable in proposing empirically testable hypotheses that follow from FMT and in describing evidence from available literature testing these hypotheses. The core tenets reflect the view that impactful fashion marketing moderates the relationships among price and consumer demand for the firm's offering (i.e., brand) by psychological customer segments, and subsequently firm profitability. Relating to fashion marketing, “psychology” in “economic psychology” includes the influences of chronic desire for conspicuous consumption (CC) and desire for rarity as relative human conditions, that is, humans vary in these desires; consumers relatively very high versus very low in these desires are more prone to enact conspicuous choices whatever the price level of the object or service. Consequently, different pricing points (decisions) that maximize profitability vary considerably for product designs which are positioned high in CC and rarity directed to customers very high in chronic desire for CC and rarity versus product designs which are positioned low in CC and rarity directed to customers very low in chronic desire for CC and rarity.